ASPEK KEPERILAKUAN DALAM PENERAPAN TEKNOLOGI INFORMASI (STUDI PADA INSTANSI PEMERINTAH DI PURWOKERTO) - Pramono Hari Adi; Ade Irma Anggraeni; Alisa Tri Nawarini (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
Technological role in various of organisational activity aspects get to be understood since technology emphasizes on information system arrangement with computer purpose, information technology can meet the need information with meteoric, timely, relevant, and accurate. Public service by government institution expected getting better and efficient,so that need developed. This research intent to test information system acceptance model on government institution at Purwokerto by use of twenty institutions and as much 176 samples. Method that is utilized for analyzing is Structural Equational Model (SEM). Result that is reached from this research points out that influential external variable to purpose easy perception and easy perception ascendant purpose to usefull perception.